Estudo da toxidade e atividade antitumoral do óleo essencial de Croton Polyandrus Spreng. (Euphorbiaceae) em Modelo Experimental de Tumor Ascítico de Ehrlich. - Pessoa, Déborah Ribeiro (2013)
Cancer, a complex genetic disease is usually the result of a multifactor process which leads to successive gene changes affecting proliferation, differentiation, and cell death. Natural products are widely used in cancer therapy, and they continue to be a promising source for new anticancer agents. Croton polyandrus Spreng., known popularly as croton de tabuleiro is rarely (either in of phytochemical or pharmacological terms) reported in the literature. Recent studies have shown its antifungal activity, but no in vitro antitumor effects for the leaf s essential oil (whose major component is p-cymene), have been reported. The present study aimed to evaluate the essential oil, extracted from the leaves of C. polyandrus (O.E.C.) for in vivo antitumor activity and toxicity. Hemolysis assay with mouse erythrocytes obtained a CH50 value of 141.0 μg/mL, suggesting moderate cytotoxicity for non-tumor cells that are typically affected during cancer therapy. In acute toxicological testing with mice, the estimated LD50 was 447.18 mg/kg. When O.E.C. was acutely administrated, CNS depressive effects were observed as well as reductions in the body weights of the animals with dosages at 250 and 375 mg/kg. Although not displaying in vitro antitumor activity, as also demonstrated for ascites carcinoma cells in the Ehrlich cytotoxicity assay (IC50 = 270.6μg/ml), O.E.C. showed significant in vivo activity, in the same cell line after nine days of treatment with 100 and 150 mg/kg oil, this considering the parameters of volume, weight and tumor cell viability. There was no significant difference between the effect produced by the oil at doses of 100 and 150 mg/kg, and that produced by 5-FU (the standard drug treatment) at 25 mg/kg. There was a significant increase in the percentage of cells found in either late apoptosis or necrosis after nine days of treatment using both doses of oil. While analyzing the distribution of cells during differing phases of the cell cycle, it was observed that O.E.C. induced cycle arrest at the G0/G1 phase, and increased the sub-G1 fraction, suggesting an induction of cell death through apoptosis. There was also an increase in the median survival rate for the animals with transplanted Ehrlich tumor. The toxicological analyzes revealed (after nine days of treatment) reductions in body weight, increased activity of transaminases (AST and ALT), and hematological changes suggestive of anemia. A decrease was seen in the leukocyte and lymphocyte counts, and a thymus index reduction, which together suggest the immunosuppressive effects commonly observed after anticancer therapy. Histopathologic analysis confirmed O.E.C. hepatotoxicity at 150 mg/kg. However, the damage was moderate and reversible, and O.E.C. did not induce an increase in micronucleated erythrocytes, implying non-genotoxicity. The results for O.E.C. indicate antitumor activity in vivo with moderate toxicity, thus suggesting further preclinical study.